PRACTICE AND THEORY OF SOCIAL WORK IN CASE STUDY OF THE REHABILITATION OF DRUG VICTIMS CLIENTS IN IPWL ANKN SURABAYA - Yulianto, Fadly (Indonesian Journal of Social Work, 2023)
Every social worker when doing social work practice. All of this cannot be separated from the need to provide good services to individuals, groups and communities so that social problems can be resolved properly. The values ​​and ethics of social work in Indonesia are currently regulated in the Code of Ethics for the Social Work Profession or commonly called the Kodepeksos which was created by the Indonesian Professional Social Worker Association (IPSPI) and is also regulated in Law Number 14 of 2019 concerning Social Workers. In practice, there are still ethical dilemmas that occur in the field. Social work principles that are always applied by social workers often face serious challenges from the conditions in the field. The client as the need for social welfare services is the main goal in an intervention. In applying these values ​​and ethics, social workers are expected to apply the principles of social work. So that the main goal in social services can be given to the maximum to the client. In addition, another goal is to prevent social workers from committing malpractice to the clients being handled.